2016
DOI: 10.1016/j.fct.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Allergenicity attributes of different peanut market types

Abstract: a b s t r a c tFour different market classes of peanut (Runner, Virginia Spanish, and Valencia) are commonly consumed in Western countries, but for some consumers peanuts are a main cause of food-induced anaphylaxis. Limited information is available on the comparative allergenicity of these distinct market classes. The aim of this study was to compare allergenicity attributes of different peanut cultivars.The protein content and protein profiles were highly comparable for all tested cultivars. All cultivar sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 42 publications
1
33
0
2
Order By: Relevance
“…On SDS‐PAGE, reduction of Ara h 3 resulted in a separation of a series of Ara h 3 polypeptides, ranging from approximately 15‐45 kDa, which are held together by one disulfide bridge under native conditions (Figure ) . Band assignments were made based on the electrophoretic mobility of peanut extract and its individual components, as was described by Koppelman et al for reducing and non‐reducing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…On SDS‐PAGE, reduction of Ara h 3 resulted in a separation of a series of Ara h 3 polypeptides, ranging from approximately 15‐45 kDa, which are held together by one disulfide bridge under native conditions (Figure ) . Band assignments were made based on the electrophoretic mobility of peanut extract and its individual components, as was described by Koppelman et al for reducing and non‐reducing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…1 Using samples from the study reported by Sampson et al, 1 the current report evaluates the serological changes in children treated with either a peanut patch (250 mg peanut protein, referred to as 250-mg patch; n 5 25) or a placebo patch (n 5 26). Similar to the protein composition of peanut, 3 the 250-mg patch contains small amounts of Ara h 6 and Ara h 2, larger amounts of Ara h 1, while Ara h 3 is the most abundant protein (see Table E1 in this article's Online Repository at www.jacionline.org). The report by Sampson et al 1 showed that treatment with the 250-mg patch induced IgG 4 to total peanut protein, and in this study, we sought to investigate the specificity of the IgG 4 induction by assessing IgG 4 to peanut components following treatment.…”
Section: Epicutaneous Immunotherapy For Peanut Allergy Modifies Igg 4mentioning
confidence: 94%
“…The functional significance of mobilized EoPs remains unclear, but it has been postulated that these cells propagate local tissue eosinophilia through in situ proliferation and maturation into eosinophils and secretion of IL-5. [3][4][5] Moreover, studies using isolated peripheral blood CD34 1 hematopoietic stem/progenitor cells have demonstrated that these cells can be potent producers of T H 2 cytokines, particularly IL-13. 6 Consequently, EoPs may be participating in propagating T H 2 inflammatory responses.…”
Section: Eosinophil Progenitor Levels Correlate With Tissue Pathologymentioning
confidence: 99%
“…This material has a protein content of 50% w / w . The purified peanut allergens, namely, Ara h1, Ara h2, Ara h3, and Ara h6, were obtained from lyophilized stock preparations and were used for the identification of bands on sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), as described earlier [ 15 , 16 ]. For the calculation of the percentage recovery of individual peanut allergens, the mean w / w percentages of these allergens in Runner-type peanuts were used [ 16 ], taking into account the protein content of the flour (50%) and of intact peanuts [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The samples were diluted at least 10-fold; the different dissolution buffers had a negligible effect on the assay using this dilution. The protein profiles of the samples were analyzed by SDS-PAGE, essentially as described earlier [ 16 ], using 10–20% gradient gels at reducing conditions. The gels were stained with Coomassie Brilliant Blue R250.…”
Section: Methodsmentioning
confidence: 99%